Head lice as vectors of pathogenic microorganisms - Hermann Feldmeier (Tropical Medicine and Health, 2023)
Abstract Body lice and head lice are the most common ectoparasites of humans. Head lice (Pediculus humanus capitis) occur worldwide in children and their caretakers, irrespective of their social status. In contrast, body lice (Pediculus humanus corporis) are confined to marginalized population groups in countries of the Global South, homeless people, and refugees. Body lice are known to transmit an array of bacterial pathogens, such as R. prowazekii, R. rickettsii, C. burneti, B. quintana, B. recurrentis, and Y. pestis. The vector capacity of head lice is still a matter of debate. The objective of the review was to scrutinize the existing evidence on the vector capacity of head lice for the transmission of bacterial pathogens. The PUBMED database was searched using a combination of the terms “pediculus humanus” OR “body lice” OR “head lice” AND “pathogen” OR “Rickettsia prowazekii” OR “Bartonella quintana” OR “Borrelia recurrentis” OR “Coxiella burneti” without a time limit. Data from epidemiological studies as well as historical observations demonstrate that body lice and head lice can carry the same array of pathogens. Since the presence of a bacterial pathogen in an arthropod is not sufficient to state that it can be transmitted to humans, and since experimental models are lacking, as yet one cannot conclude with certainty that head lice serve as vectors, although this review presents circumstantial evidence that they do. Adequately designed experimental and epidemiological studies are needed to ascertain the exact transmission potential of head lice.